A longitudinal assessment on the development of financial fraud offending. Issue 4 (10th June 2020) - Rima, Dzhansarayeva; Yerbol, Alimkulov; Ali, Baissalov; Liliya, Bissengali; Beaver, Kevin
Abstract : Purpose: Fraudulent behaviors have a significant influence on society, impact millions of citizens and result in billions of dollars in losses. Consequently, it is essential to understand the potential correlates and causes of financial fraud offending. To date, however, there has not been much research examining the developmental origins to financial fraud offending. The purpose of this study is to address this gap in the literature. Design/methodology/approach: Longitudinal data drawn from the National Longitudinal Study of Adolescent to Adult Health were analyzed. The measures of socialization and individual differences were assessed in adolescence, and then examined to determine whether they predicted the odds of credit card and check frauds in adulthood. Findings: The results revealed that the measures of parental socialization were unrelated to later-life financial fraud. Associating with delinquent peers was associated with financial fraud in some of the models as was low self-control and nonviolent propensities. Practical implications: In this study, the authors discuss the implications of the current study and offer suggestions for future research. Originality/value: To the best of authors' knowledge, this is one of the first studies to examine the developmental unfolding of fraud offending in a nationally representative sample.